Improved arithmetic coding for Time-Warped MDCT based audio coding - Bayer, Stefan; Edler, Bernd (Proceedings of the IEEE 2013 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2013)
The Time-Warped Modified Discrete Cosine Transform (TW-MDCT) improves the energy compaction for harmonic signals with varying fundamental frequency compared to the plain MDCT. Adaptive context based entropy coding has the potential to provide higher gain over memoryless entropy coding. But in combination with the TW-MDCT, the context based adaptive coding may lead to suboptimal coding. This paper presents an algorithm for improving the context for the TW-MDCT. This is mainly achieved by exploiting already available information on the frequency variation needed by the TW-MDCT. This results in an improved entropy coding.<br
Keywords: Context; Harmonic analysis; Time-frequency analysis; Audio coding; Bit rate; Speech; Audio Coding; Entropy Coding; TW-MDCT; Arithmetic Coding